Isolation of an Antifungal Compound from Anaphalis sinica Hance - Yang, Lingyun; Yu, Zhiyi; Zhang, Xingang; Fan, Jieyu; Chen, Mingjing; Deng, Hui; Hou, Taiping; Tao, Ke (Asian Journal of Chemistry, 2012)
The present investigation was in order to isolate antifungal constituents from Anaphalis sinica Hance, using activity against several phytopathogenic fungi as a lead. Bioactivity guided fractionation of the petroleum ether extract has led to the isolation of a tremetone derivative (compound 1), whose structure had been elucidated as 4,6-dihydroxy-14,14-dimethyltremeton based on extensive 1D and 2D NMR and HR-ESI-MS spectral data. Compound 1 had exhibited excellent antifungal activity against Valsa mali, Elsinoe ampelina and Gibberella saubinetii and the values of their EC50 reached 2.27, 7.18 and 12.30 μg/mL respectively, that was comparable to the commercial fungicide carbendazim, whose EC50 values were 1.60, 33.54 and 6.60 μg/mL respectively.